Transformacja europejskiego kompleksu bezpieczeństwa - Kostecki, Wojciech (Przegląd Strategiczny, 2016)
The main goal of the article is an attempt to outline an analytical tool that would systematize considerations of the possible variants of the development of the European Union as a result of a coincidence of internal and external circumstances. Prospects of further progress, stop, and fall of integration, impacts of the proceedings of Russia and changes in the broader international environment are taken into account. For this purpose an approach developed by the influential mainstream research, called the Copenhagen school, has been implemented: the theory of security complexes.